Analysis of Shopee Live Discount Vouchers and Sales Promotions on Impulse Buying at Madam Gie Through Content Marketing as a Mediating Variable (A Study on Gen Z Shopee Users in Sukabumi City) - Hermawati, Irma; Danial, R. Deni Muhammad; Komariah, Kokom (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The advancement of digital technology and the rising popularity of live streaming features on e-commerce platforms have significantly altered consumer behavior, particularly among Generation Z. Shopee, as the most widely used marketplace by Gen Z in Indonesia, offers Shopee Live, a feature that combines real-time promotional discounts with engaging content. One local cosmetic brand that actively utilizes this feature is Madam Gie. This study aims to examine the influence of voucher discounts and sales promotion on impulse buying behavior among Gen Z Shopee users in Sukabumi, with content marketing as a mediating variable. A quantitative research approach was employed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Data were collected from 200 respondents who had made at least one purchase on Shopee within the last three months. The results reveal that both voucher discounts and sales promotion significantly and positively influence impulse buying behavior. Furthermore, content marketing plays a significant mediating role, and strengthening the effect of promotional strategies on impulsive purchase decisions.